Administering the inherited ‘employment miracle’: the labour market policy of the second Merkel government - Bandau, Frank; Dümig, Kathrin (German politics, 2014)
Contrary to most other OECD countries, the German labour market remained almost unaffected by the consequences of the global financial crisis and experienced a strong and steady recovery. Thus, after their victory in the elections of 2009, the economic conditions for the bourgeois parties to shape labour market policy according to their preferences were rather favourable. After exploring the causes of the German ‘employment miracle’, this article summarises the relevant labour market policies introduced by the black-yellow coalition. We argue that, apart from some important exceptions, the second Merkel government did not pursue a decidedly market-liberal policy agenda. Instead, primarily due to the low problem load, the government mainly readjusted some of the existing policy instruments. Therefore, German labour market policy between 2009 and 2013 can rather be described as an administration of the inherited ‘employment miracle’ than an active pursuit of a discrete policy agenda.
Gesehen am 14.07.2020